2023
DOI: 10.1007/s40615-023-01806-z
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on African Migrants’ Wellbeing, and Their Coping Strategies in Urban and Regional New South Wales, Australia: a Qualitative Study

Peter Bai James,
Kathomi Gatwiri,
Lillian Mwanri
et al.

Abstract: Aim As the COVID-19 pandemic response continues to evolve, the need to protect more vulnerable populations in society becomes more apparent. Studies are still emerging on how different population groups have been impacted by the COVID-19 pandemic. Our study explored the impact of COVID-19 for African migrants in New South Wales, Australia, and their coping strategies. Methods We employed inductive, exploratory qualitative interpretive research design using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, reports on loneliness among migrants during the COVID-19 pandemic are limited. A study with 21 African migrants in New South Wales, Australia, reported that the COVID-19 lockdown had a signi cant impact on African communities and disrupted their sense of community, leading to loneliness [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, reports on loneliness among migrants during the COVID-19 pandemic are limited. A study with 21 African migrants in New South Wales, Australia, reported that the COVID-19 lockdown had a signi cant impact on African communities and disrupted their sense of community, leading to loneliness [27].…”
Section: Discussionmentioning
confidence: 99%